DIGITAL COMPETITIVENESS IN THE BANKING SECTOR OF BANGLADESH - Bhuiyan, Md. Mazharul Islam; Imran, Md. Ali; Rahid, Abu Obida (International Journal of Business and Management Future, 2022)
Digital competitiveness is the capacity of an economy to adopt and explore digital technologies leading to the transformation in government practices and banking models by obtaining the ability to keep up with trends, explore new technologies and change the way we do things. Digital competitiveness has been rising in modern banking, and this trend will likely stay the same for a while. The study examines the technologies used by the banking sector and how the escalation of its application transpired from 2014 to 2020. The present study is mainly based on secondary data collected from the sample unit, and results are interpreted in tabular form, bar, and pie chart using SPSS and MS Excel. The results reveal how, functionally, the banking sector in Bangladesh is flourishing using modern technologies. That shows digitally; our banking system is getting competitive. Digitalization is becoming more popular in our economy, and that’s why our banks are working to contribute to modern society’s mechanization. Most of our private and state-owned banks practice renovated software for better services. This automation in the banking sector is flourishing the activities and compensating our tempo. JEL Classification Codes: G21, G32, E-58.